2010
DOI: 10.1158/0008-5472.can-09-3578
|View full text |Cite
|
Sign up to set email alerts
|

Responses in Mantle Cell Lymphoma Cells to SNS-032 Depend on the Biological Context of Each Cell Line

Abstract: SNS-032 is a potent inhibitor of cyclin-dependent kinases (Cdk) 2, 7, and 9 that regulate the cell cycle and transcription. Our studies in indolent primary chronic lymphocytic leukemia cells showed that SNS-032 inhibited transcription, diminished the antiapoptotic protein Mcl-1, and induced apoptosis. The present study focuses on evaluating this compound in four proliferating mantle cell lymphoma lines (Jeko-1, Granta 519, Mino, and SP-53). Consistent with its action against Cdk9 and Cdk7, SNS-032 inhibited th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…17,18 To examine whether cyclin D was decreased by S14161 via the CDK9 signaling pathway, we checked expression of CDK9 in the myeloma cell lines LP1 and OPM2. CDK9 was decreased by S14161 in both LP1 and OPM2 cells within 24 hours in a concentration-dependent manner ( Figure 1H), which further demonstrated that S14161 regulates cyclin D on the transcriptional level.…”
Section: Identification Of Small-molecule Inhibitors Of D-cyclins By mentioning
confidence: 99%
“…17,18 To examine whether cyclin D was decreased by S14161 via the CDK9 signaling pathway, we checked expression of CDK9 in the myeloma cell lines LP1 and OPM2. CDK9 was decreased by S14161 in both LP1 and OPM2 cells within 24 hours in a concentration-dependent manner ( Figure 1H), which further demonstrated that S14161 regulates cyclin D on the transcriptional level.…”
Section: Identification Of Small-molecule Inhibitors Of D-cyclins By mentioning
confidence: 99%
“…SCH727965 (dinaciclib), a novel inhibitor of CDK1, -2, -5, and -9, showed superior activity and an improved therapeutic index compared with flavopiridol in laboratory models of solid and hematologic malignancies (61,62) and was the subject of intense investigation in numerous clinical trials (63)(64)(65). However, preliminary data did not show a dramatic response to these CDK inhibitors, suggesting that other deregulated pathways are contributing to the growth and survival advantages of aggressive MCL cells compared with normal cells (8,33,34).…”
Section: Targeting Underlying Cell-cycle Dysregulation In Mcl: Cdk Inmentioning
confidence: 99%
“…On the other hand, high-level p27 expression is associated with better survival (26,32), again supporting the notion that MCL is a disease characterized by gross cell-cycle dysregulation at a variety of levels, and that the level of dysregulation correlates with prognosis. Finally, direct inhibition of the expression of cyclin D1 can be achieved in the laboratory by short-hairpin RNA targeting cyclin D1, and has been shown to reduce proliferation and clonogenic survival of MCL cells (8,33,34).…”
Section: Introductionmentioning
confidence: 99%
“…19 The dysregulation of the cell-cycle machinery suggests that inhibition of CDK4 should have antiproliferative effects in MCL, and has prompted the preclinical and clinical evaluation of CDK inhibitors in this disease. The agents tested to date, including flavopiridol, 20,21 seliciclib, 22 and SNS-032, 23 have greater potency against other CDK family members, including the transcriptional CDK9, and may be of interest for their ability to deplete antiapoptotic proteins from malignant hematopoietic cells. 14 PD0332991, a potent, selective CDK 4/6 inhibitor, causes G 1 arrest in MCL and other cell lines by blocking phosphorylation of Rb at CDK4/6-specific sites, including Ser 807/811 and Ser 780 .…”
Section: Introductionmentioning
confidence: 99%